Treatment for Refractory Pancreatic Cancer - Makrilia, Nektaria; Syrigos, Kostas N; Saif, Muhammad W (JOP. Journal of the Pancreas, 2011)
While gemcitabine-based regimens are currently accepted as the standard first-line treatment of patients with locally advanced or metastatic pancreatic adenocarcinoma, there is no consensus regarding treatment in the second-line setting. This review is an update from the 2011 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium regarding recent developments in the treatment of refractory pancreatic cancer, as these were presented in Abstracts #237 and #272 of the meeting. Image: Sophia Engastromenou Schliemann (the founder of the "Sotiria"/"Salvation" Hospital) wearing the "Jewels of Helen" (photograph taken ca. 1874).